1975
DOI: 10.1017/s0022029900015284
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrate as a substrate for the determination of lipase activity in milk

Abstract: SummaryA procedure is described for the determination of the lipolytic activity in milk using tributyrate as substrate. The method is based on the titration of liberated butyric acid in a diethyl ether: light petroleum (2·75:1, v/v) extract of the incubation mixture. Some of the fundamental factors involved in the procedure are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Antisera to the purified milk enzyme cross-react with the LPL in human post-heparin plasma and human milk 36 and inhibit essentially all of the tributyrinase activity in milk. 20 From this latter fact and from the similarity in response of the lipase (tributyrinase) and lipoprotein lipase activities to various agents such as NaCl, heat and light it has been concluded that both activities can be attributed to the same enzyme molecule and that this is the only major lipolytic enzyme in bovine milk,2(l-2,37 Flynn and Fox 38 compared milk lipase purified by the method of Fox and Tarassuk 16 with the LPL purified on heparin-Sepharose and concluded that both procedures yielded the same enzyme. Some workers have however expressed the view that there are two different milk lipases.…”
Section: Bovine Milk Lipasementioning
confidence: 99%
See 1 more Smart Citation
“…Antisera to the purified milk enzyme cross-react with the LPL in human post-heparin plasma and human milk 36 and inhibit essentially all of the tributyrinase activity in milk. 20 From this latter fact and from the similarity in response of the lipase (tributyrinase) and lipoprotein lipase activities to various agents such as NaCl, heat and light it has been concluded that both activities can be attributed to the same enzyme molecule and that this is the only major lipolytic enzyme in bovine milk,2(l-2,37 Flynn and Fox 38 compared milk lipase purified by the method of Fox and Tarassuk 16 with the LPL purified on heparin-Sepharose and concluded that both procedures yielded the same enzyme. Some workers have however expressed the view that there are two different milk lipases.…”
Section: Bovine Milk Lipasementioning
confidence: 99%
“…48 The role of the milk fat globule membrane may be a rather complex regulatory one since it contains both activating lipoproteins 72 and inhibiting glycoproteins. 75 Following the discovery that the major lipolytic enzyme in milk was a lipoprotein lipase 20 and that lipolysis could be initiated in any milk by the addition of blood serum or serum lipoproteins,312 it was suggested that spontaneous milk contained activating cofactors derived from the blood. 90 Some considered that these cofactors might be small (MW c. 10 000) soluble apo-LPs which could leak into the milk from the blood during periods of stress.…”
Section: Biochemical Aspectsmentioning
confidence: 99%
“…Indeed, in an early report on lipase assays using tributyrin as a substrate, basecatalysed hydrolysis of tributyrin above pH 7 increased exponentially with increasing pH (Castberg, Solberg, & Egelrud, 1975). By varying the pH of the buffer used in the assay and measuring non-enzymatic hydrolysis, we found that this trend is still evident below pH 7 for tributyrin, triheptanoin and trioctanoin (Fig.…”
Section: Assay Phmentioning
confidence: 61%
“…Over the pH range 7.0-6.6, the effect of a change in pH on enzymic activity (12) was also minimized. Moreover, a neutral pH avoids autolysis of TBG, which does not become significant until pH ~8 (21,22). Thus, pH ĩ 7.0 meets requirements to best advantage and avoids other problems, such as general acid-or base-catalyzed hydrolysis.…”
Section: Resultsmentioning
confidence: 99%